การขับเคลื่อนกระบวนการชุมชนแห่งการเรียนรู้ทางวิชาชีพเพื่อพัฒนาความสามารถในการจัดการเรียนรู้ของนักศึกษาวิชาชีพครู มหาวิทยาลัยธนบุรี - ศักดิ์บุญญารัตน์, ธัญญพัทธ์; เทศปลื้ม, มาริษา; บุญประกอบ, มนัส; มาตรพรหม, ลือศักดิ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: 1) examine the effects of the Professional Learning Community (PLC) process on the learning management competencies of pre-service teachers, and 2) explore guidelines for promoting the learning management competencies of pre-service teachers through the PLC process. A mixed-methods research design was employed. The study involved the entire population of 238 participants, including pre-service teachers, mentor teachers, and university supervisors. The research instruments consisted of a learning management competency assessment form, PLC activity records, and focus group discussion records. Quantitative data were analyzed using mean, standard deviation, percentage, and relative gain scores, while qualitative data were analyzed through content analysis.           The results revealed that: 1) the learning management competencies of pre-service teachers improved continuously after participating in the PLC process. The mean relative gain score increased from 0.35 to 0.51. The proportion of participants with high and very high levels of development increased, while the proportion at the initial level decreased to 0.00 percent; and 2) the guidelines for promoting students’ learning management competencies through the PLC process included establishing systematic reflective practices, collaboratively identifying student learning problems based on empirical data, fostering a collaborative working culture, utilizing technology to support knowledge sharing, and developing best practices alongside appropriate assessment tools. The findings indicate that the Professional Learning Community (PLC) effectively enhances the learning management competencies of pre-service teachers. Furthermore, the study highlights key issues that can serve as guidelines for further development and future implementation of PLC-based professional learning initiatives.